Governing maximum reindeer numbers in Fennoscandia - Sarkki, Simo; Johnsen, Kathrine Ivsett; Löf, Annette; Pekkarinen, Antti Juhani; Kumpula, Jouko; Rasmus, Sirpa; Landauer, Mia; Åhman, Birgitta (2023)
This chapter examines the complexities and challenges in state governance of the maximum permitted number of reindeer in Finland, Norway and Sweden. The common findings regarding the three countries are that (1) maximum permitted numbers of reindeer set by the nation states primarily seem to promote objectives other than those of herders; (2) various contextual aspects (e.g., laws, other land users, trends in science, herding practices and historical developments) partly explain the sustainable maximum permitted numbers; (3) reductionist assessments of pasture – reindeer relations easily neglect the impacts of other land users on condition and availability of pastures, thereby making the assessments biased and stigmatizing herders for alleged overgrazing. The chapter also explores issues related to reindeer numbers that vary across the three countries including (4) herders’ opportunities to participate in knowledge production and resulting decisions over maximum reindeer numbers, (5) clashes between herders’ experience and practice-based knowledge and scientific knowledge on which the definitions of maximum numbers are often based and (6) the ways in which the borders between reindeer herding districts and nation states have implications for the governance of reindeer numbers. Peer reviewed